2004
DOI: 10.1371/journal.pbio.0020079
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Association of Functionally and Cytotopically Related mRNAs with Puf Family RNA-Binding Proteins in Yeast

Abstract: Genes encoding RNA-binding proteins are diverse and abundant in eukaryotic genomes. Although some have been shown to have roles in post-transcriptional regulation of the expression of specific genes, few of these proteins have been studied systematically. We have used an affinity tag to isolate each of the five members of the Puf family of RNA-binding proteins in Saccharomyces cerevisiae and DNA microarrays to comprehensively identify the associated mRNAs. Distinct groups of 40–220 different mRNAs with strikin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

73
1,019
4
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 604 publications
(1,098 citation statements)
references
References 69 publications
73
1,019
4
2
Order By: Relevance
“…For example, we do not know whether translation-activating signals act on the individual mRNA species or on ribonucleoprotein (RNP) complexes in which transcripts coding for proteins with complementary function are co-packaged. Association of RNA-binding proteins with discrete sets of mRNAs coding for functionally related proteins and co-existence of several mRNA species within shared RNP complexes has been unambiguously demonstrated in yeast [94,95], and is proposed to exist in eukaryotic cells [96][97][98]. If these putative post-transcriptional RNA operons exist in axons it will be an interesting idea to target the formation or the axonal transport of the multifunctional RNP in order to interfere with intra-axonal protein synthesis of a cohort of functionally related proteins.…”
Section: Perspective/challengesmentioning
confidence: 99%
“…For example, we do not know whether translation-activating signals act on the individual mRNA species or on ribonucleoprotein (RNP) complexes in which transcripts coding for proteins with complementary function are co-packaged. Association of RNA-binding proteins with discrete sets of mRNAs coding for functionally related proteins and co-existence of several mRNA species within shared RNP complexes has been unambiguously demonstrated in yeast [94,95], and is proposed to exist in eukaryotic cells [96][97][98]. If these putative post-transcriptional RNA operons exist in axons it will be an interesting idea to target the formation or the axonal transport of the multifunctional RNP in order to interfere with intra-axonal protein synthesis of a cohort of functionally related proteins.…”
Section: Perspective/challengesmentioning
confidence: 99%
“…Results from yeast, however, indicate that simple relationships are not necessarily to be expected. A survey of the binding specificities of all five S. cerevisiae Puf proteins revealed that each protein bound to a subset of mRNAs whose products appeared to be functionally linked [34]. Curiously, however, only 12 of the mRNAs that were previously described as being regulated in the PUF1-5 deletion mutant were also found bound to Pufs.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be that PUFs are needed to adapt to stressful conditions which are not encountered during culture. Several of the yeast Puf proteins had overlapping RNA-binding specificities [34]; perhaps in trypanosomes also the various PUFs have overlapping functions. In order to determine the functions of T. brucei PUF proteins it will therefore probably be necessary to determine the binding specificities of all 10 proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, during transcription elongation, the endonuclease activity of Rad2p is dispensable but the C-terminal region of the protein is important (Lee et al, 2002). In addition, RAD2 is inferred to positively regulate the expression of PUF4 (Yu et al, 2008), which regulates mRNA stability by binding to its target mRNAs (Gerber et al, 2004). Taken together, these results indicate that RAD2 is involved in other cellular functions besides damaged DNA repair as a component of the NER process.…”
Section: Introductionmentioning
confidence: 97%